Antagonisté excitacních aminokyselin a potenciace korových evokovaných potenciálů - Nanka, O (Sbornik lekarsky, 1999)
Changes of evoked potentials under the influence of NBQX (a non-NMDA receptor antagonist), MK-801 (a NMDA receptor antagonist) and GDEE (a nonselective antagonist of glutamate receptor) were studied. GDEE augmented potentiation and was marked progression of potentiation with increasing number of stimuli. There was no potentiation of responses in relation to the number of stimulus in a series in experiments with both MK-801 and NBQX. Interpretation of results with NBQX and MK-801 is difficult.
Keywords: antagonisté excitačních aminokyselin; Quinoxalines; dizocilpinmaleát; AMPA receptory; Rats; Excitatory Amino Acid Antagonists; Glutamates; Animals; krysa rodu Rattus; mužské pohlaví; Male; chinoxaliny; evokované potenciály; glutamáty; Evoked Potentials; Dizocilpine Maleate; Receptors, AMPA; zvířata